Gas chromatographic-mass spectrometric analysis of polycyclic aromatic hydrocarbon metabolites in Antarctic fish ( Notothenia gibberifrons ) injected with Diesel Fuel Arctic - Wade, T. L.; Fang, J.; Yu, Y.; Brooks, J. M.; McDonald, S. (Archives of Environmental Contamination and Toxicology, 1995)
Fish (Notothenia gibberifrons) collected in pristine Antarctic sites were injected with Diesel Fuel Arctic (DFA). Gas chromatography/mass spectrometry (GC/MS) was used to identify and quantify polycyclic aromatic hydrocarbon (PAH) metabolites obtained from hydrolyzed fish bile. The concentrations of naphthols (NPH), phenanthrenols (PHN), dibenzothiophenols (DBT), and total PAH metabolites (∑PAH) vary with time. The response curve (production of PAH metabolites vs. time) resembled a Sigmoid curve, with an initial low response at 24 h followed by a rapid rise in production of PAH metabolites (55.74 μg/g) 120 h after exposure to DFA. PAH metabolites identified include NPH, PHN, and DBT and their alkylated derivatives, reflecting the composition of the DFA to which the fish were exposed. The GC/MS technique is highly sensitive, particularly in the detection of multi-ring PAH metabolites. The results suggest that analysis of PAH metabolites is a valuable tool for environmental monitoring and assessment of exposure to petroleum. Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/48081/1/244_2004_Article_BF00212975.pdf